Optimism and pessimism. Associated variables in the school context - Giménez Hernández, Montserrat (Pulso. Revista de educación, 2005)
Optimism has achieved greater importance in recent years and,nowadays, we possess enough pieces of research to be able to define it, evaluate itand work with it. This article deals with the main ideas regarding the terms ‘optimism’and ‘pessimism’ as well as with the most relevant findings concerning to them.The aim of this article is to enable teachers to access these findings buildinga connection between optimism and some of the most important concepts in theeducational system. The teacher, then, can reflect upon them with the aim ofdiscovering strategies to use in the classroom